Hubungan Motivasi Belajar dengan Hasil Belajar Siswa di Sekolah Dasar - Fimala, Yosi; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
The research aim to know there is or no correlation between students motivation in learning with learning outcomes of five grade of primary school on cluster two in Baso Subdistrict Agam District. This type of research is quantitative research with correlation research methods. The amount of sample is 30 students, five grade of primary school on cluster two in Baso Subdistrict Agam District. The result of the research there is positive correlation an significant between students motivation in learning with learning outcomes of five grade of primary school on cluster two in Baso Subdistrict Agam District. This was proven from rhitung > rtabel = 0,971>0,361, and significance 5%. Which means that Ho is rejected and Ha is accepted, so the hypothesis says "there is a correlation between students in learning motivation with learning outcomes of five grade of primary school on cluster two in Baso Subdistrict Agam District." accepted.